Trends and issues in digital libraries (2016)
The study explored trends and issues in digital libraries with a view to furnish the expected audience with current happenings in this area of operations and service delivery. The chapter is a detailed review of characteristics of digital libraries considering the creation of digital collections which include conversion of retrospective materials, born digital resources and institutional repositories. The paper considered digital collections and copyright issues, benefits and issues of digital libraries, preservation of digital content. It x-rayed trends in information discovery, access and retrieval in a digital library, human-computer interaction, information organization and categorization of digital library services.